2011
DOI: 10.1210/jc.2010-0881
|View full text |Cite
|
Sign up to set email alerts
|

TheFOXO3Ars2802292 G-Allele Associates with Improved Peripheral and Hepatic Insulin Sensitivity and Increased Skeletal Muscle-FOXO3AmRNA Expression in Twins

Abstract: Our data indicate that the minor G-allele of FOXO3A rs2802292 is associated with enhanced peripheral and hepatic insulin sensitivity in our small twin cohort, which may be mediated through increased FOXO3A mRNA expression, although no major metabolic impact of rs2802292 was found in the large Inter99 cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 19 publications
5
44
0
Order By: Relevance
“…The most familiar FOXO3A intronic SNP rs2802292 is characterized by a G to T transversion. A twin cohort study suggested that carriers of the minor G allele of rs2802292 showed reduced fasting plasma insulin and lower incremental area under the curve 0–120 min for insulin following oral glucose loading compared with non-carriers, indicating that the minor G allele was associated with enhanced peripheral and hepatic insulin sensitivity, possibly mediated through increased FOXO3A mRNA expression 25. Improved insulin sensitivity has been considered as a feature of long-lived individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The most familiar FOXO3A intronic SNP rs2802292 is characterized by a G to T transversion. A twin cohort study suggested that carriers of the minor G allele of rs2802292 showed reduced fasting plasma insulin and lower incremental area under the curve 0–120 min for insulin following oral glucose loading compared with non-carriers, indicating that the minor G allele was associated with enhanced peripheral and hepatic insulin sensitivity, possibly mediated through increased FOXO3A mRNA expression 25. Improved insulin sensitivity has been considered as a feature of long-lived individuals.…”
Section: Discussionmentioning
confidence: 99%
“…But whether these variants also play a role in the pathogenesis of type 2 diabetes has not been yet studied. Additionally, one study also reported that the minor allele of the SNP rs2802292 in FOXO3 is associated with improved peripheral and hepatic insulin sensitivity in twins (Banasik et al, 2011). In this study we have carried out a detailed case control analysis of common variants in FOXO3 using haplotype tagging SNP approach for association with type 2 diabetes and related biochemical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Functional DAF-16, the worm FOXO transcription factor, has been demonstrated to be required for the longevity of many of the lifespan enhancing mutations [39]; [40]. Interestingly, human population studies have revealed an association between single nucleotide polymorphisms (SNPs) in human FOXO3 and human lifespan extension [41]; [42] [43]; [44]) and the strength of the association appears to increase with age [45]. Therefore, FOXO3 appears to be a candidate longevity gene in humans and thus demonstrates how work in the humble nematode worm can inform on the biology of human ageing.…”
Section: Wormsmentioning
confidence: 99%